O ensino de transformações químicas em ambiente não-formal: ênfase na produção de açúcar e álcool - Azevedo, Cristian Fernando (2017)
The contextualization in the teaching of chemistry is indispensable for the comprehension of the expressions of the concepts in the school with the daily life. The research carried out and evaluated the process of teaching learning for the students of the third year of high school of the State School Coselheiro Gavião Peixoto in relation to the concepts on the subject of chemical transformations. What is, therefore, is to provide a more comprehensive approach of a contextualized approach that allows to respond, which learning variables promoted from the study of the productive system of sugar and alcohol. The data collection was based on questionnaires, flowchart, visit to the community, the name of the group of students and the answers of the professor researcher during the development of all the research and the accomplishment of a series of activities a plant. The analysis of the data was performed in a qualitative approach, both the pre-verbal and post-questionnaire questionnaires of a categorical analysis were presented as having been on a course that the students developed the skills and competences necessary for the chemical change of a The physical transformation and the decision-making capacity regarding environmental and social issues in relation to the means of production. The empowerment of students during project activities, especially during the week they promote, school reform, school of activities and learning of teaching-learning.